Kesiapan Pemerintah Dalam Menghadapi Digitalisasi Televisi Menurut Perspektif Organisasi Pembelajar - P Nurtrio Harjessi; Martani Huseini (Politeknik Negeri Bengkalis, 2019)
Television digitization is an internationally agreed consensus. Government readiness is needed to face the changes and technological developments. One perspective that can be used to face television digitalization is by forming a learning organization. Basically, learning organizations formed by the government involving all stakeholders will produce readiness in television digitalization, although challenges and obstacles are often found in the formation of these learning organizations. Constraints faced can be in the form of legal issues in the form of lawsuits and resistance due to lack of learning and the involvement of all parties in technological change. This paper uses the method of analysis of literature studies through books, journals, reports, and publications related to government readiness in facing television digitalization in accordance with the perspective of the learning organization. The results of the analysis indicate that the perspective of the learning organization can be one of the solutions to face television digitalization, such as the formation of a task force that is being carried out by the government by involving all stakeholders as a forum for learning. Besides that the government is trying to prepare its organization to face television digitalization with several efforts such as drafting the government's version of the Broadcasting Law; developing guidelines for digital broadcasting blueprints; establishment of working groups for the preparation of analog to digital TV migration; conducting socialization and promotion; conducting studies on the preparation of digital TV business opportunities to the stipulation of Ministerial Decrees on Digital Broadcast Trials.